Singing the Psalms : applying principles of African music to bible translation - Dickie, June F. (Scriptura : Journal for Contextual Hermeneutics in Southern Africa, 2017)
Psalms were composed to be sung, and translated psalms should also be carefully constructed so that they are easily singable. This requires an understanding of the features of (indigenous) song and rhythm. Towards that end, this article seeks to summarise some important principles of African (particularly Zulu) music, and indicates some errors made in the past by translators of biblical material to be sung. Then some examples are given from a recent study which attempted to apply these principles to the translation of some biblical Psalms into isiZulu. The hope is that sensitivity to such musical features will facilitate a translation that communicates all the aesthetic beauty, rhetorical power, and memorability of the original.